2016
DOI: 10.1111/den.12692
|View full text |Cite
|
Sign up to set email alerts
|

Heparin‐bridging therapy is associated with a high risk of post‐polypectomy bleeding regardless of polyp size

Abstract: Heparin-bridging therapy is associated with a high risk of PPB regardless of polyp size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 28 publications
(74 reference statements)
3
28
0
Order By: Relevance
“…Among the antithrombotic agents, HB therapy has been reported to be a strong risk factor for PPB [7,15,30,31]. Ishigami et al [31] reported that the OR of PPB in patients treated with HB was 9.8 compared with that of patients without antithrombotic treatment. This result was comparable with our study, in that patients with HB showed a much higher PPB risk than those without antithrombotic agents (OR 33.1 per patient, 17.3 per lesion).…”
Section: Discussionmentioning
confidence: 99%
“…Among the antithrombotic agents, HB therapy has been reported to be a strong risk factor for PPB [7,15,30,31]. Ishigami et al [31] reported that the OR of PPB in patients treated with HB was 9.8 compared with that of patients without antithrombotic treatment. This result was comparable with our study, in that patients with HB showed a much higher PPB risk than those without antithrombotic agents (OR 33.1 per patient, 17.3 per lesion).…”
Section: Discussionmentioning
confidence: 99%
“…Based on this guideline, HBT is considered a treatment option for patients who are undergoing colorectal EMR or ESD in the presence of antithrombotic therapy. However, recent retrospective studies addressing the safety and efficacy of HBT in colorectal EMR and EP revealed that HBT increases rather than decreases the risk of POB [22][23][24] . Consistent with the studies cited above, the rate of POB following colorectal ESD tended to be higher in our HBT group than in our no-HBT group, although the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, anticoagulants or antiplatelet agents must be discontinued in patients bearing a low risk of thromboembolism following withdrawal or replaced by heparin bridge therapy (HBT) in patients at high risk of thromboembolism following withdrawal before endoscopic procedures with a high risk of bleeding, such as EMR and ESD [21] . Recent retrospective studies addressing the safety and efficacy of HBT in colorectal EMR and EP revealed that HBT increases rather than decreases the risk of POB [22][23][24] . It should be noted, however, that clinical studies addressing the safety and efficacy of HBT in colorectal ESD are not available.…”
Section: Introductionmentioning
confidence: 99%
“…Inoue et al[14] demonstrated that the incidence of PPB was significantly higher in a heparin bridge group than in a non-heparin bridge group (20.0% vs 1.4%, respectively). Ishigami et al[22] also demonstrated that heparin-bridging therapy is associated with a high risk of PPB regardless of polyp size.…”
Section: Discussionmentioning
confidence: 99%